Overweight and Obesity Among Lower-Grade Elementary Schools in Donggala, Gorontalo, Indonesia - Pomatahu, Aisah R (Universitas Negeri Gorontalo, 2023)
Obesity and overweight are two different things. The aim of this activity is to analyze data on the incidence of obesity and overweight among primary school children. Carried out in elementary schools in Donggala, this activity applies observational methods to analyze the BMI of lower-grade elementary schools. Based on the results, it was found that the incidence of overweight and obesity was 5.38% and 12.90%. in addition, very thin and thin nutritional status were detected.